Study on kinetics and thermsodynamics of municipal solid waste incineration fly ash in air and N2 atmospheres - Yegui Wang; Weifang Chen; Na Zhao; Yifan Chen; Baoqing Deng (PLoS ONE, 2025)
This study attempted to investigate the thermal behavior and reaction mechanisms of municipal solid waste incineration fly ash under air and N2. Mass loss patterns at temperatures from 30ºC to 1100ºC were obtained through thermogravimetric analysis. Based on mass loss patterns, the behavior of fly ash under high temperature was divided into three stages. Mass loss in Stage I (30ºC-500ºC) amounted to 3.0%-6.2%. The majority of mass loss concentrated in Stage II (500ºC-800ºC) and Stage III (800ºC-1100ºC). Kinetic parameters of fly ash in Stage II and Stage III were evaluated using Flynn-Wall-Ozawa (FWO), Kissinger-Akahira-Sunose (KAS), and Friedman methods. By comparison, the iso-conversional FWO method exhibited the highest correlation coefficient with R2 > 0.99. Activation energy (E) values in Stage II calculated via the FWO method indicate that reaction in air showed considerably higher hurdle (E = 171.11 kJ/mol) than reaction in N2 (E = 124.52 kJ/mol). This difference was partly attributed to the presence of carbonation process in air. In contrast, E values in Stage III were similar with E of 373.38 kJ/mol in air and 382.25 kJ/mol in N2. Mechanistic analysis via the Coats-Redfern (CR) model, employing 15 kinetic functions, identified dominant mechanisms of one-dimensional diffusion and contracting sphere for Stage II in air and N2 respectively. At the same time, three-dimensional diffusion could best explain the reaction mechanism in Stage III in both air and N2. Moreover, calculations of thermodynamic parameters (ΔH, ΔG, and ΔS) revealed that major reactions of fly ash during thermal treatment were endothermic and non-spontaneous, with Stage III exhibiting heightened complexity. This multi-stage characterization elucidates the degradation mechanisms of fly ash under varying thermal conditions and provides useful insight into the fly ash thermal treatment processes.